Practical Security Automation and Testing Tools and Techniques for Automated Security Scanning and Testing in DevSecOps. - Hsu, Tony Hsiang-Chih (Packt Publishing Ltd, 2019)
Security automation is the automatic handling of software security assessments tasks. This book helps you to build your security automation framework to scan for vulnerabilities without human intervention.